2023
DOI: 10.1111/wre.12571
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of finger weeder safety and efficacy for intra‐row weed removal in irrigated field crops

Abstract: Increased demand for pesticide‐free food and the development of herbicide‐resistant weed populations have created a need for non‐chemical weed‐control tools. A candidate mechanical tool for controlling weeds in the seeding line (intra‐row zone) is the finger weeder. This study thus aimed to evaluate the safety and weed‐control efficacy of the finger weeder in various irrigated field crops. Eight field trials were conducted in processing tomato, sweet corn, sunflower, cotton, and beetroot over 2 years. The fing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Any management program that use the finger weeder should combine complementary means for well-established and non-sensitive species that escape the application of this tool. This premise aligns with a previous study demonstrating that optimal weed-control results were achieved when the finger weeder was combined with herbicide application (Asaf et al, 2023). It is also in agreement with other studies evaluating nonchemical weed-control tools that demonstrated optimal results when these tools were integrated with other control tools (Harker & O'Donovan, 2013;Melander et al, 2005;Pannacci & Tei, 2014;Perotti et al, 2020).…”
Section: Sensitivity Evaluationsupporting
confidence: 92%
See 1 more Smart Citation
“…Any management program that use the finger weeder should combine complementary means for well-established and non-sensitive species that escape the application of this tool. This premise aligns with a previous study demonstrating that optimal weed-control results were achieved when the finger weeder was combined with herbicide application (Asaf et al, 2023). It is also in agreement with other studies evaluating nonchemical weed-control tools that demonstrated optimal results when these tools were integrated with other control tools (Harker & O'Donovan, 2013;Melander et al, 2005;Pannacci & Tei, 2014;Perotti et al, 2020).…”
Section: Sensitivity Evaluationsupporting
confidence: 92%
“…Finger weeders are available in various versions, with fingers of different sizes and different degrees of hardness, which can be tailored to particular soil types, crops, and seeding distances (Melander et al, 2015). A previous study showed that repeated application of the finger weeder resulted in adequate weed control result in a wide range of vegetable and field crops, that was not inferior compared to herbicides-based treatments (Asaf et al, 2023).…”
mentioning
confidence: 99%
“…Recent assessments have explored the pre-emergence application of herbicides like metribuzin 52 and pendimethalin 53 along with the utilization of a finger weeder for mechanical intra-row weed control. 54 We are aware that the results of the current study were acquired under controlled environmental conditions, and it is, therefore, essential to extend the study to evaluate weed management on a field scale, as is currently taking place in fields in the study region.…”
Section: Discussionmentioning
confidence: 99%
“…The manifold possibilities of mechanical weed control including ploughing, harrowing and hoeing require considerable expertise and investment and are more dependent on environmental influences than chemical measures. Implements for the selective removal of weeds between crop rows such as finger weeders must be used in the early growth stages of the weed and are highly effective for weed species with shallow and compact root systems, such as A. sterilis (Asaf et al, 2023). Camera‐steered hoes with a hydraulic side shifting control are widely available for row crops, however, sensor‐based technology for precision mechanical weed control is still in development (Machleb et al, 2020).…”
Section: Options For Reducing Glyphosate Use In Europementioning
confidence: 99%